Pengaruh Pemberian Tepung Indigofera Sebagai Pengganti Bungkil Kedelai Dan Dedak Dalam Ransum Terhadap Performa Produksi Entog (Cairina Moschata) - Ali Nasyeh; Dini Widianingrum; Rachmat Somanjaya (Tropical Livestock Science Journal, 2023)
This research was conducted in March - August 2021, located in Darma District, Kuningan Regency, West Java Province, Indonesia, which is located at the coordinates 7°02°09.4 "South Latitude 108°24'24'20.6' East Longitude. The purpose of this study was to analyze the effect of indigofera flour on the performance muscovy duck. The research was conducted experimentally using the Completely Randomized Design (CRD) 80 muscovy duck were drawn to be placed in a cage which was divided into 20 sections consisting of 4 muscovy duck. The types of treatment used were P0 (basal ration) as control, P1 25% indigofera flour, P2 50% indigofera flour, P3 75% indigofera flour and P4 100% indigofera flour as a substitute for soybean meal and rice bran. The variables observed were ration consumption, weight gain, ration conversion and feed cost per gain. The research data were analyzed using variance (Anova) and if there was a significant difference, then further tested using Duncan's multiple distance test (DMRT). The results showed that the use of indigofera flor cold increase (P<0,05) feed consumption, this is due to the nutrient content in the ratio and the variables of weight gain, ration conversion and feed cost per gain did not show a significant difference (P>0,05). It can be concluted that the effect of the addition of indigofera as a subtitute for soybean meal and bran can increase ration consumption but is not followed by optimal grain performance.